A novel insight to screen the optimal spray-drying protectants and parameters for manufacturing lactic acid bacteria preparations. Issue 14 (1st October 2020) - Zhang, Zhuo; Peng, Sen; Sun, Xiaoqi; Jie, Yu; Zhao, Hongfei; Zhu, Baoqing; Dziugan, Piotr; Zhang, Bolin
Abstract: This study constructed a β-galactosidase (β-gal) liposome model instead of bacterial cells to optimize spray-drying protectants and parameters. The screened protectant combination consisted of 35 g/L monosodium glutamate, 50 g/L sucrose, and 35 g/L maltodextrin. The optimal parameters for spray drying were 130 °C inlet air temperature, 7.5 mL/min feed flow rate, and 150 mL optimal protectant combination. The viability of the five lactic acid bacteria strains spray-dried with the optimized protectant and parameters was over 50%. Lactobacillus helveticus strain LH-9's mechanism of resistance to spray-dry treatment was investigated in the presence of the optimal protectant combination.